Debate: When it Comes to Modern Slavery, do Definitions Matter? - David, Fiona (Anti-Trafficking Review, 2015)
On the 3rd of April 2015, Indonesian government officials visited the remote island village of Benjina.[1] This followed press reports by Associated Press (AP) that Burmese men were being kept on Benjina island in cages, beaten with stingray tails and paid little or nothing, to fish for a company that occupies the port on the island, Pusaka Benjina Resources. [1] R McDowell and M Mason, ‘AP Investigation Prompts Emergency Rescue of 300 Plus Slaves’, AP, 3 April 2015, retrieved 23 July 2015, http://bigstory.ap.org/article/197048ef871f4b56b4a129d0e3c0f129/fishermen-rush-be-rescued-amid-indonesian-slavery-probe